2016
DOI: 10.1038/emm.2016.64
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory versus suppressive effects of GM-CSF on tumor progression in multiple cancer types

Abstract: Granulocyte-macrophage colony-stimulating factor (GM-CSF, also called CSF-2) is best known for its critical role in immune modulation and hematopoiesis. A large body of experimental evidence indicates that GM-CSF, which is frequently upregulated in multiple types of human cancers, effectively marks cancer cells with a ‘danger flag' for the immune system. In this context, most studies have focused on its function as an immunomodulator, namely its ability to stimulate dendritic cell (DC) maturation and monocyte/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
145
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(155 citation statements)
references
References 99 publications
5
145
0
5
Order By: Relevance
“…Although our studies focus on the role of CD11b + DC at secondary sites, these cells also infiltrate primary tumors and thus may play a role in PDAC initiation and progression at the primary site. Our results reinforce the pathophysiological function of tumor-derived GM-CSF in PDAC (16, 17) and potentially other GM-CSF-producing cancers (49), finding that it drives Gr1 + /Ly6C + Mo to differentiate into CD11b + DC that express PD-1 ligands and expand Treg. Consistent with these findings, expression levels of MGL and PD-L2 correlate with DC markers, Foxp3, and GM-CSF and its receptor in human PDAC specimens.…”
Section: Discussionsupporting
confidence: 81%
“…Although our studies focus on the role of CD11b + DC at secondary sites, these cells also infiltrate primary tumors and thus may play a role in PDAC initiation and progression at the primary site. Our results reinforce the pathophysiological function of tumor-derived GM-CSF in PDAC (16, 17) and potentially other GM-CSF-producing cancers (49), finding that it drives Gr1 + /Ly6C + Mo to differentiate into CD11b + DC that express PD-1 ligands and expand Treg. Consistent with these findings, expression levels of MGL and PD-L2 correlate with DC markers, Foxp3, and GM-CSF and its receptor in human PDAC specimens.…”
Section: Discussionsupporting
confidence: 81%
“…Studies have shown that GM-CSF can support tumor clearance through promoting DC maturation and antigen presentation, such as in the setting of HER-2 targeted vaccination. However, GM-CSF in the absence of targeted tumor antigen, such as in the GM-SCF-secreting mock vaccine, may support tumor growth through immune suppression [37,38]. This could explain the reduced rate of tumor clearance observed with 3T3GM combined with sorafenib.…”
Section: Discussionmentioning
confidence: 99%
“…Abrogation of leukocytes with chemotherapy drugs is life-threatening for patients with cancer (19). Although granulocyte macrophage-colony-stimulating factor is usually effective in raising leukocyte count following chemotherapy, its cost and side effects pose a challenge for patients (20). In a previous study, PFTS significantly enhanced peripheral leukocytes and almost completely reversed the leukopenia in mice induced by cyclophosphamide, to a similar level to that mediated by G. lucidum, a well-known immune activator (21).…”
Section: Discussionmentioning
confidence: 99%